1968
DOI: 10.1126/science.160.3830.879
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Isotope Ratios in Phosphate from Fossil Marine Organisms

Abstract: Well-preserved fossil marine organisms generally yield very positive delta(18)(PO(4)(3-)) values which are considered to result from relatively good preservation of the original oxygen-isotope composition of phosphatic material deposited under isotopic equilibrium conditions in oceanic water whose O(18):O(16) ratio was more positive than that of modern oceans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…It was originally hoped that a phosphatle thermometer might provide accurate calibration for the oxygen thermometer, but recent work has shown that although the oxygen isotope ratio of phosphate is temperature-dependent, the calculated carbonate/phosphate fractionation seems to be practically independent of temperature (Longindli, 1965;Longinelli and Sordi, 1966;Longinelli and Nuti, 1968). As a result, the isotopic composition of ancient seas cannot be determined by this method.…”
Section: (3) the Isotopic Composition Of The Original Sea Watermentioning
confidence: 99%
“…It was originally hoped that a phosphatle thermometer might provide accurate calibration for the oxygen thermometer, but recent work has shown that although the oxygen isotope ratio of phosphate is temperature-dependent, the calculated carbonate/phosphate fractionation seems to be practically independent of temperature (Longindli, 1965;Longinelli and Sordi, 1966;Longinelli and Nuti, 1968). As a result, the isotopic composition of ancient seas cannot be determined by this method.…”
Section: (3) the Isotopic Composition Of The Original Sea Watermentioning
confidence: 99%
“…However, the P-O bond can be easily broken in enzyme-mediated biochemical reactions [Dahms and Boyer, 1973;Boyer, 1978]. Oxygen isotope ratios of phosphate in apatite from marine and terrestrial vertebrates and invertebrates indicate that biogenic apatite precipitates in isotopic equilibrium with environmental water at the temperature of deposition [Longinelli, 1966;Longinelli and Nuti, 1968;Kolodny et al, 1983;Shemesh et al, 1983;Luz et al, 1984]. Bacterially mediated fractionation between P-bound oxygen and water appears to be governed by equilibrium reactions rather than kinetic factors, and the temperature-dependent isotopic equilibrium of apatite precipitated in microbial culture experiments with ambient water is the same as for apatite in marine and terrestrial vertebrates and invertebrates [Blake et al, 1998].…”
Section: Oxygen Isotopic Composition Of Phosphatementioning
confidence: 99%
“…Several authors have not agreed with the above assumption and suggested instead the possibility of a progressive depletion in Ol 8 in sea water going back in time (Silverman, 1951;Craig, 1965;Longinelli, 1966;Longinelli and Nuti, 1968). With regard to the Quaternary, Emiliani (1955) has attempted to evaluate the possible variation of the isotopic composition of oceanic water between glacial and interglacial periods; however, Dansgaard and Tauber (1969) and other authors have disputed his conclusions, mainly on the basis that the isotopic composition of ice from the Greenland ice cap cores is much more negative during glacial periods than that evaluated by Emiliani for his calculation.…”
Section: Changes In the Isotopic Composition Of Oceanic Watermentioning
confidence: 99%
“…Although it is difficult to advance hypotheses regarding isotopic compositional changes for the preglacial Pleistocene and the Pliocene, some data are available. For instance, Longinelli and Nuti (1968), on the basis of oxygen isotope measurements carried out on the phospate in Upper Tertiary fossils, have suggested that a major depletion in the 018 o f Mediterranean water took place from Miocene to Pliocene times. The cause is not entirely understood, but is perhaps related to the extensive formation of evaporites throughout the Mediterranean in the late Miocene (see Chapter 43) leading to an 018 excess followed by a sudden replacement of normal marine conditions in the Lower Pliocene.…”
Section: Past Variations In the Isotopic Compositionmentioning
confidence: 99%
See 1 more Smart Citation